The Naked bear : folktales of the Iroquois - Bierhorst, John; Zimmer, Dirk (Morrow, 1987)
A collection of sixteen traditional tales told by the Iroquois Indians, some featuring talking animals and some presenting terrifying flesh-eating creatures such as the Naked Bear, the Stone Coat, and the Whirlwinds.